1997
DOI: 10.1128/iai.65.11.4832-4835.1997
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae infection induces inflammatory changes in the aortas of rabbits

Abstract: Chlamydia pneumoniae, a common human respiratory pathogen, has been associated with atherosclerosis in several seroepidemiological studies. Moreover, its presence in lesions of vessel walls has been demonstrated by culture, immunohistochemistry, PCR, and electron microscopy. In this study, we infected intranasally with C. pneumoniae New Zealand White rabbits which had been fed a normal diet. Reinfection was given 3 weeks later. Six of the nine reinfected animals showed inflammatory changes consisting of intima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
6

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(56 citation statements)
references
References 38 publications
2
48
0
6
Order By: Relevance
“…Other micro-organism infections, including Chlamydia pneumonia are reported to induce aortic inflammation. 80,81 Vascular involvement was not reported in IL-12B deficient mice, 82 but the antiangiogenic effect of IL-12 is widely reported. 83,84 IL-12-expressing tumor cells show low metastasis ability.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Other micro-organism infections, including Chlamydia pneumonia are reported to induce aortic inflammation. 80,81 Vascular involvement was not reported in IL-12B deficient mice, 82 but the antiangiogenic effect of IL-12 is widely reported. 83,84 IL-12-expressing tumor cells show low metastasis ability.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Initially, seroepidemiological evidence indicated an association between CP and atherosclerosis and, subsequently, this intracellular pathogen was detected in atherosclerotic lesions [139,[153][154][155][156][157][158][159][160] and ruptured plaques [161]. Accordingly, CP was proposed to play a role in the pathogenesis of vascular disease, possibly by inducing a low-grade inflammation in the arterial wall [162][163][164][165][166], and there was great hope that antibiotic treatment might prevent acute cardiac problems in patients with coronary artery disease (CAD). However, although initial pilot studies in humans and experimental animal models appeared promising [167], a number of extensive clinical studies employing antibiotics for the primary or secondary prevention of coronary heart disease have failed to provide adequate evidence for the efficacy of such treatment (reviewed in [168]).…”
Section: Hcmv Infection In Patients With Vascular Diseasesmentioning
confidence: 99%
“…In a variety of animal experimental models, repeated infection with C. pneumoniae through the respiratory tract demonstrates induction of early atherosclerotic lesions or accelerated progression of atherosclerosis in the aorta [52][53][54]. Studies in both rabbits and mice have demonstrated a potential interaction between infection with C. pneumoniae and elevated serum lipids resulting from dietary and/or genetic factors [55][56][57][58][59].…”
Section: I R E C T I S O L a T I O N O F C P N E U M O N I A E I mentioning
confidence: 99%